Greenhouse gas savings and energy balance of sewage sludge treated through an enhanced intermediate pyrolysis screw reactor combined with a reforming process. (15th May 2019) - Marazza, Diego; Macrelli, Stefano; D'Angeli, Mirta; Righi, Serena; Hornung, Andreas; Contin, Andrea
Highlights: A catalytic thermo-chemical process (TCR®) is applied to sewage sludge-to-energy. Energy and GHG assessment focus on optional Anaerobic Digestion before TCR®. Full system modelling and MonteCarlo sensitivity analysis are performed. TCR® treatment of undigested sludge provides a net energy of 2 MJ/kg of d.a.f. sludge. Greenhouse gas emission credits of 0.5 kgCO2 eq/kg of d.a.f. sludge are obtained. Abstract: A life cycle thinking approach focusing on energy and greenhouse gas savings has been applied to study the potential for energy recovery and organic matter reclamation from Waste Activated Sludge produced in Waste Water Treatment Plants by means of a catalytic thermo-chemical process. A generic Basic Sludge Processing line has been modelled following common waste water and sludge treatment stages found in several European plants. This has served to identify and divide generic sludge treatment units in order to compare the performance of different industrial configurations where a specific thermo-chemical technology treatment unit and related cogeneration was substituted or added to reference units. The considered technology is an enhanced intermediate pyrolysis screw reactor combined with a reforming process known as Thermo-Catalytic Reforming allowing for conversion of sewage sludge into energy carriers and reclamation of organic substances in the form of charcoal (biochar). In order to study the greenhouse gas savings, a calculator tool complying with Directive 2009/28/EC has been adopted. Results show that substantial benefits in terms of energy production and greenhouse gas emissions reduction of a sludge-to-energy system are expected if the secondary sludge is directly treated with the Thermo-Catalytic Reforming process, without an intermediate anaerobic digestion step.